Trastuzumab: Updated Mechanisms of Action and Resistance in Breast Cancer - Claret, Francois X.; Vu, Thuy T. (Frontiers in Oncology, 2012)
HER2-postitive breast cancer has the second-poorest prognosis among breast cancer subtypes. One of the most effective targeted therapies for patients with HER2-positive breast cancer is trastuzumab-based. However, primary or acquired resistance to trastuzumab has been a major obstacle in the clinical management of this disease. Therefore, to better control HER2-postitive breast cancer, it is necessary to gain a deeper understanding of trastuzumab’s actions and the pathways that cancer cells use to “dodge” its effects. In this review, we attempt to give an overview of the widely accepted and currently proposed molecular mechanisms for these actions and highlight recent advances in our understanding of HER2 targeted therapies.